1997
DOI: 10.1055/s-0038-1637863
|View full text |Cite
|
Sign up to set email alerts
|

The Requirements of an Electronic Medical Record to Suit all Clinical Disciplines

Abstract: The design of the electronic medical record is becoming increasingly Sophisticated as techniques develop to improve the understanding of user requirements. Such techniques must develop as it becomes increasingly important to improve the use and uptake of such records. An outstanding question is whether the same electronic medical record can fulfil the requirements of users in different clinical disciplines. To evaluate such a requirement it is necessary to understand the different information management the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Usually, such systems have one level of "objective information" and another single level of "meta-information". This metainformation is often related to patients' problems (9,14,15,17,18). Even within these two-layered models, there is not always a clear-cut distinction between the two levels under consideration: what is "meta-information" (interpretation) and what is "observation" (facts) (19).…”
Section: Discussionmentioning
confidence: 99%
“…Usually, such systems have one level of "objective information" and another single level of "meta-information". This metainformation is often related to patients' problems (9,14,15,17,18). Even within these two-layered models, there is not always a clear-cut distinction between the two levels under consideration: what is "meta-information" (interpretation) and what is "observation" (facts) (19).…”
Section: Discussionmentioning
confidence: 99%
“…Poorly designed interfaces can slow user performance and possibly distract them from the main purpose of their activity. Hayes [9] has reported that users experience difficulty and dissatisfaction when interacting with a poorly designed interface that has an excessive number of icons, menus, or options; re-quires the user to remember lengthy complex commands; and/or offers insufficient navigational control.…”
Section: Figure 3 Represents Headache Screen For Patients To Select mentioning
confidence: 99%
“…Nowadays, the healthcare delivery model has switched to a collaborative team approach and patients are often treated by a team of healthcare professionals from the three different sectors of care: primary, secondary and tertiary (known as a multidisciplinary approach); 5 as a result, EPRSs have evolved to collect, hold and maintain required information across the three sectors.…”
Section: Introductionmentioning
confidence: 99%